2015
DOI: 10.1002/cyto.a.22800
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma‐mesenchymal stem cell communication modulates expression patterns of kinin receptors: Possible involvement of bradykinin in information flow

Abstract: The most aggressive subtype of brain tumors is glioma WHO grade IV, the glioblastoma (GBM). The present work aims to elucidate the role of kinin receptors in interactions between GBM cells and mesenchymal stem cells (MSC). The GBM cell line U87-MG was stably transfected to express dsRed protein, single cell cloned, expanded, and cultured with MSC, both in the direct co-cultures (DC) and indirect co-cultures (IC) at equal cell number ratio for 72 h. Up-and down-regulation of matrix metalloproteases (MMP)29 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 43 publications
(46 reference statements)
4
39
0
Order By: Relevance
“…Authentication of the cell lines was performed as described previously [7]. U373 cells stably expressing enhanced green fluorescent protein (U373 eGFP cells) [24] and U87 cells expressing red fluorescent protein (dsRED) were prepared as described previously [59]. …”
Section: Methodsmentioning
confidence: 99%
“…Authentication of the cell lines was performed as described previously [7]. U373 cells stably expressing enhanced green fluorescent protein (U373 eGFP cells) [24] and U87 cells expressing red fluorescent protein (dsRED) were prepared as described previously [59]. …”
Section: Methodsmentioning
confidence: 99%
“…However, for patients who have increasing edema unresponsive to steroids, there are few additional medical therapies available. is, combined with recent research that supports bradykinin's role in both tumor invasion and vasogenic edema, has led to interest in the usefulness of C1INH as a potential therapy to decrease the amount of bradykinin generated by malignant glioblastoma cells [3,4,11]. Our case discusses a patient with advanced glioblastoma who had diffuse angioedema refractory to steroid therapy who responded well to plasma-derived C1INH replacement.…”
Section: Introductionmentioning
confidence: 92%
“…Prognosis is deemed as poor, with 5year survival after radiation and temozolomide chemotherapy at 9.8% [2]. It is thought that mesenchymal stem cells influence glioblastoma invasiveness through crosstalk pathways that lead to an upregulation of bradykinin, a vasoactive peptide, and its receptors: bradykinin 1 receptor (B1R) and bradykinin 2 receptor (B2R) [3,4]. B1R receptors are more highly expressed in pathological processes involving tissue damage [5], while B2R are constitutive throughout the body and when expressed on brain tissue, play a role in the regulation of the BBB [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies have demonstrated the role of BK in neurite outgrowth, proliferation inhibition of stem cells and their differentiation into neurons (Martins et al, 2005;Trujillo et al, 2009;Trujillo et al, 2012;Nascimento et al, 2015;Pillat et al, 2015). At a molecular level, BK and B2BKR are also involved in ERK activation, acting via tyrosine kinases Pyk2 and Src (Ca 2+ -dependent pathway), and via EGF and PKC pathway, respectively (Dikic et al, 1996;Adomeit et al, 1999).…”
Section: Bradykinin and Neurogenesismentioning
confidence: 99%